Development of Video-Based Qur’anic Tilawah Learning Media to Improve Students’ Tilawah Skills at Baabul Umam Islamic Boarding School - Hasnah Azhari; Zulhimma, Zulhimma; Hasibuan, Zainal Efendi (Jurnal Pendidikan Agama Islam Indonesia (JPAII), 2026)
Purpose of the study: This study aims to develop a video-based Qur’anic recitation (tilawah) learning medium to enhance the artistic recitation skills of students at Baabul Umam Islamic Boarding School, Hajoran Village, Sungai Kanan District. Methodology: The method employed in this study is Research and Development (R&D) using the ADDIE model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. The study adopts a mixed-methods approach, in which qualitative data are utilized to analyze learning needs and contextual conditions, while quantitative data are used to measure the validity, practicality, and effectiveness of the developed media. Main Findings: The findings indicate that the developed media demonstrate a very high level of validity, with percentages of 98% from subject matter experts, 90% from media experts, and 92% from instructional experts. The practicality level is categorized as very practical, as reflected by teachers’ responses at 96% and students’ responses at 93.87%. Furthermore, the effectiveness of the media falls into the highly effective category, with an N-Gain score of 0.83. Novelty/Originality of this study: The novelty of this study lies in the development of a video-based Qur’anic recitation (tilawah) learning medium that is contextually designed to meet the needs of students. This medium integrates aspects of tajwid, makharij al-huruf, and the melodic art of tilawah in an audio-visual format. This study offers an innovative approach to enhancing students’ artistic Qur’anic recitation skills and enriches instructional methods within Islamic boarding school environments effectively.